Heat exchange system and method - Parbs, Timothy James; Deacon, Walter T (2019)
A dual fluid heat exchange system is presented that provides a stable output temperature for a heated fluid while minimizing the output temperature of a cooled fluid. The heated and cooled fluids are brought into thermal contact with each other within a tank. The output temperature of the warmed fluid is maintained at a stable temperature by a re-circulation loop that connects directly to the mid portion of the tank such that the re-circulated fluid flow primarily warms only a re-circulation section of the tank. The other, lower flow rate, section of the tank may be positioned so that it has a cooler temperature and thus serves to increase the efficiency of the heat exchange by extracting extra heat energy out of the cooled fluid before it leaves the tank. Alternatively, the low flow rate section of the tank may be warmer than the re-circulated section, and thus allow the re-circulated section to be cooler than the output temperature of the warmed fluid.